Racial Discrimination in The Great Debaters Movie - Rifqi, Arif; Harida, Ratri; Ro’is, Syamsuddin (STKIP PGRI Ponorogo Press, 2025)
The Great Debaters serves as a powerful cinematic text that offers a multifaceted exploration of racial injustice and intellectual resistance through the strategic deployment of racist utterances—whether in the form of slurs, threats, institutionalized policies, or internalized oppression. The movie lays bare the linguistic mechanisms that reinforce racial hierarchies and social marginalization. The 26 utterances function as discursive acts that reflect and reproduce unequal power relations, as revealed through a critical discourse analysis grounded in Fairclough’s model. Through the utterances, the viewers gain insight into the normalization of racism through everyday language and institutional discourse. One example of this was the juxtaposition of brutal historical references (such as the Willie Lynch narrative) with moments of rhetorical resistance (e.g., the assertion of Black identity and intellectual agency in debate scenes) that illuminates the ongoing struggle over meaning, representation, and voice. The movie acts as both a historical recounting and a pedagogical tool, inviting critical engagement with how language constructs racial identities and sustains systemic injustice. As a medium of reasoned argument, persuasion, and public voice, the utterances of the Wiley College debate team demonstrated a form of social activism and identity reclamation. This framing enables educators and students alike to connect historical struggles for civil rights with contemporary discourses surrounding race, equity, and education.